Analysis of Depletion Region Width and Breakdown Voltages of 6H-SiC DIMOSFET Using Linearly Graded Profile in the Drift Region - Sharma, Indra Mani (My University, 2011)
The thesis work carried out here on 6H-Silicon Carbide Double Implanted Power MOSFET has been an attempt to understand the analysis of the depletion region width and breakdown voltages for various types of doping profiles in the drift region of the device. The doping profiles used are primarily uniformly doped and linearly graded doping profile in the drift region.The ultimate aim for making this study is to provide a graded profile in the drift region of the MOSFET with lower doping at the top of the device near the source to a higher doping near the drain. This type of profile will help in increasing the breakdown voltage. Breakdown voltages selected for the purpose of analysis ranges from 1kV to 20 kV. It has been established that the linearly graded device can be used easily to obtain much higher values of critical electric field than uniformly doped device. For linearly graded devices with precalculated device heights, it was found that Punch through and Avalanche breakdown voltages were almost equal for all values of gradients and Neff for linearly graded DIMOSFETs. This can be verified from Table 5.6. However this type of tally is not seen in the case of uniformly doped devices as shown in Table 4.4. Here breakdown voltages Vbpt and Vbav are found to be nearly equal only in the case of doping level of 1015 /cc for Vbpt of 5kV, 10kV and doping level of 1016 /cc for Vbpt of 1kV. Equivalence of these two breakdown voltages have not been established for other doping levels and breakdown voltages. It has been shown that at the expense of an increase in the depletion region width of uniformly doped drift region devices of 6H-SiC DIMOSFET, the magnitude of critical field Ec and Vbpt and Vbav can be significantly increased by decreasing the magnitude of the concentration gradient in the drift region.
M.Tech. (VLSI Design and CAD)
Keywords: Silicon Carbide; Analysis of Depletion Region Width and Breakdown Voltages; Drift Region